The 2,3-DPG levels of human red blood cells during an incremental exercise test: relationship to the blood acid-base balance - Spodaryk, K; Zoladz, J A (Physiological research, 1998)
The aim of this study was to evaluate the influence of exercise with the intensity progressively increasing from rest until maximal oxygen uptake (VO2max) on 2,3-DPG levels in red blood cells (RBC) in relation to the changes in the acid-base balance and plasma lactate concentration. Six healthy young men (age 22.5+/-1.5 years, VO2max 3.48+/-0.20 l/min) participated in this study. The subjects performed an incremental exercise test on a cycloergometer until exhaustion. Blood samples were tested for acid-base balance indices (pH, HCO3-, BE), plasma lactate and RBC 2,3-DPG concentration. Gas exchange variables were measured continuously breath-by-breath. In this paper we present data concerning 2,3-DPG, plasma lactate, pH, HCO3- and BE measured at rest, at the power output corresponding to the lactate threshold (PO LT), at the power output at maximal oxygen uptake (PO VO2max), as well as 5, 15 and 30 min after finishing the incremental test. Increase of power output above the lactate threshold to the PO VO2max was accompanied by a significant (p<0.01) increase of plasma lactate from 2.58+/-0.78 mmol/l to 10.22+/-3.04 mmol/l. This was also accompanied by a significant drop (p<0.01) in blood pH value from 7.352+/-0.025 at the PO LT to 7.294+/-0.041 at the PO VO2max. No significant changes of the RBC 2,3-DPG level were observed at any of the analysed stages of the exercise. The RBC 2,3-DPG level expressed in relation to the changes of haematocrit showed only minor changes during the exercise period and after 15 min of recovery vs. resting value (3.21+/-1.19). However, after 30 min of recovery, RBC 2,3-DPG decreased to the value of 2.32+/-1.19 micromol/ml. We conclude that, during an incremental test, no increase in RBC 2,3-DPG concentration is required to reach the maximal oxygen uptake level. Moreover, a rapid decrease in blood pH, developing during a single bout of exercise, is not a stimulus powerful enough to cause significant changes in the RBC 2,3-DPG level during short-term exercise.
Keywords: mužské pohlaví; Exercise Test; Male; Erythrocytes; Humans; Oxygen Consumption; spotřeba kyslíku; Osmolar Concentration; lidé; Blood; Lactic Acid; 2,3-difosfoglycerát; krev; 2,3-Diphosphoglycerate; osmolární koncentrace; acidobazická rovnováha; Differential Threshold; dospělí; diferenční práh; Acid-Base Equilibrium; Adult; zátěžový test; kyselina mléčná; erytrocyty